The Russian economy at a turning point: As the war boom ends, the Kremlin faces growing economic risks - Janis Kluge (Stiftung Wissenschaft und Politik (SWP), 2024)
Russia plans to significantly step up its military spending once again in 2025. Both the production of weapons and the recruitment of soldiers are becoming increasingly expensive. Over the past two years, strong government demand has triggered a war boom in parts of the Russian economy. Incomes have risen and there is new optimism about the economy. However, owing to labour shortages and the impact of Western sanctions, economic growth has stalled this year, while inflation has remained stubbornly elevated. The Central Bank is using very high interest rates to fight price increases, which is creating more headwinds for the economy but has so far failed to slow inflation. Amid the deteriorating outlook for the Russian economy in 2025, the country is more vulnerable to economic crises. New sanctions or a drop in oil prices could trigger a recession.
Keywords: 320; Russia; military spending; war against Ukraine; inflation; Central Bank; price increases; economic crises; sanctions; military-industrial complex